Dynamic Isolation Technologies in Negative Pressure Isolation Wards - Xu, Zhonglin; Zhou, Bin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents novel design principles and technologies for dynamic isolation based on experimental studies. These approaches have now become the local standard in Beijing and are currently being promoted for use nationwide. Further, the book provides details of measures and guidelines for the design process. Departing from the traditional understanding that isolation wards should be designed with high negative pressure, airtight doors and fresh air, it establishes the basis for designing biological clean rooms, including isolation wards, using a simple and convenient scientific approach. This book is intended for designers, engineers, researchers, hospital management staff and graduate students in heating ventilation air conditioning (HVAC), air cleaning technologies and related areas.
Importance of negative pressure isolation ward -- Three misunderstandings in design process of negative pressure isolation ward -- Principle and technology of dynamic isolation -- Air distribution design in negative pressure isolation ward -- Determination of air change rate in negative pressure isolation ward -- Safety of exhaust and return air is prerequisite -- Design essentials for negative pressure isolation ward.
Keywords: Buildings -- Environmental engineering; Continuum mechanics; Pollution; Practice of medicine; Hospitals -- Administration; Building Physics, HVAC; Continuum Mechanics; Pollution; Practice and Hospital Management